The Impact of Meaningful Work on Employee Engagement: The Case of Mongolian Kindergarten Teachers - Zanabazar, Altanchimeg; Dugersuren, Altanchimeg; Maligar, Byambasuren (Advances in Social Sciences Research Journal, 2024)
Numerous studies substantiate the correlation between meaningful work and its far-reaching impact on various aspects of employees' lives. This includes bolstering financial stability, improving physical health, nurturing relationships, and fostering a sense of community. Consequently, these positive outcomes ripple into elevated levels of job satisfaction, increased work engagement, and enhanced job retention. The primary objective of this study is to explore the relationship between meaningful work and employee engagement. The study utilized data from 149 employees across four private kindergartens in Ulaanbaatar city of Mongolia and conducted thorough analyses to evaluate the reliability and correlation of variables, employing covariance-based structural equation modeling (CB-SEM). The analysis revealed that the positive meaning has a significant and positive correlation with all three facets of employee engagement. Notably, positive meaning has moderate positive impacts on cognitive engagement (β = 0.531), emotional engagement (β = 0.549), and behavioral engagement (β = 0.546) among the participants. Additionally, the research findings revealed that meaning-making through work displayed small yet statistically significant positive effects on various aspects of employee engagement among kindergarten employees. Specifically, meaning-making through work weak and positively influenced cognitive engagement (β = 0.479), emotional engagement (β = 0.395), and behavioral engagement (β = 0.408). Furthermore, the research findings revealed that the greater good motivations had the strongest positive relationship with employee engagement among the three facets assessed. Specifically, greater good motivations showed substantially positive effects on cognitive engagement (β = 0.751), emotional engagement (β = 0.859), and behavioral engagement (β = 0.763) among the kindergarten teachers.